An Integrative Assessment Combining Deep-Sea Net Sampling, in situ Observations and Environmental DNA Analysis Identifies Cabo Verde as a Cephalopod Biodiversity Hotspot in the Atlantic Ocean - Merten, Véronique; Bayer, Till; Reusch, Thorsten B. H.; Puebla, Oscar; Fuss, Janina; Stefanschitz, Julia; Lischka, Alexandra; Hauss, Helena; Neitzel, Philipp; Piatkowski, Uwe; Czudaj, Stephanie; Christiansen, Bernd; et al. (Frontiers in Marine Science, 2021)
The deep sea is among the largest, most biologically diverse, but least-explored ecosystems on Earth. Baseline information on deep-sea biodiversity is crucial for understanding ecosystem functioning and for detecting community changes. Here, we established a baseline of cephalopod diversity and distribution off Cabo Verde, an archipelago in the eastern tropical Atlantic. This baseline served to test the hypothesis that Cabo Verde is biogeographically separated from other Macaronesian islands and allowed us to identify cephalopods that may play a role in the Macaronesian carbon cycle and oceanic food web. To investigate cephalopod diversity, we used 746 individual cephalopods obtained by nets (0 - 1000 m) and 52 cephalopod encounters during video surveys with a towed camera (0 - 2500 m) and manned submersible (0 - 375 m). Additionally, environmental DNA (eDNA) metabarcoding on 168 seawater samples (50 - 2500 m), using an 18S rRNA universal cephalopod primer pair, and a species-specific primer pair for Taningia danae resulted in the detection of 32 taxa. All three methods combined detected a total of 88 taxa including 48 species. Each method contributed between 7 and 54 % of taxa that were not detected by the other methods, indicating that multiple approaches are needed for deep-sea cephalopod biodiversity assessments. We document six species and three genera for the first time around Cabo Verde.Video surveys and eDNA analysis detected Taningia danae recurrently (100 - 2500 m). eDNA metabarcoding proved to be a powerful tool for biodiversity monitoring and as a complement to traditional sampling methods. When including literature records, Cabo Verde hosts 103 cephalopod taxa including 30 families and 65 benthic and pelagic species. The total number and species composition of Cabo Verde cephalopods is similar to the Canary Islands and Azores, two known cephalopod biodiversity hotspots, but the Cabo Verde octopus composition is different. Due to a range of life history characteristics, we hypothesize that the squids Taningia danae and Sthenoteuthis pteropus are important in the carbon cycle of Macaronesia. As a cephalopod biodiversity hotspot Cabo Verde could function as a model region to investigate cephalopod biology and ecology in a rapidly changing Atlantic Ocean.